2008
DOI: 10.1080/01434630802147916
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Family Language Policy and Heritage Language Knowledge Among Second Generation Russian–Jewish Immigrants in Israel

Abstract: The family unit and home domain have been and remain important in heritage language maintenance efforts. There are complex relationships between parental language attitudes, their application in everyday language management activities and the children's knowledge of home language vocabulary. The present large-scale study examined the family policy factors affecting first language (L1) maintenance among second generation Russian Á Jewish immigrants in Israel in light of Spolsky's (2004) model of language policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
82
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(91 citation statements)
references
References 14 publications
4
82
0
5
Order By: Relevance
“…This suggests that parents can play a crucial role in the heritage language development of their children, even if the children are exposed to a majority language early on in life, since the parents of young heritage speakers are their main and maybe only source of family language input, and so their preference for using the heritage language in the family and thus for providing their children with opportunities to acquire this language can be expected to make a difference. The results of the current study thus support the findings of many studies that demonstrated that immigrant parents' attitude towards the family language and their language practices play a crucial role in the heritage language proficiency of their children (e.g., Pearson 2007;Park & Sarkar 2007;Schwartz 2008). The present findings particularly underscores the role parents can play if their children were born in or emigrated to the host country at a very young age.…”
Section: Conclusion Implications and Limitationssupporting
confidence: 92%
“…This suggests that parents can play a crucial role in the heritage language development of their children, even if the children are exposed to a majority language early on in life, since the parents of young heritage speakers are their main and maybe only source of family language input, and so their preference for using the heritage language in the family and thus for providing their children with opportunities to acquire this language can be expected to make a difference. The results of the current study thus support the findings of many studies that demonstrated that immigrant parents' attitude towards the family language and their language practices play a crucial role in the heritage language proficiency of their children (e.g., Pearson 2007;Park & Sarkar 2007;Schwartz 2008). The present findings particularly underscores the role parents can play if their children were born in or emigrated to the host country at a very young age.…”
Section: Conclusion Implications and Limitationssupporting
confidence: 92%
“…De Houwer 1999;King 2000;Curdt-Christiansen 2016). Schwartz (2008), for example, found that even though most of the Hebrew-Russian families who participated in her study had positive attitudes towards the preservation of Russian, only 27% reported doing reading instruction at home. In other words, parents' attitudes and beliefs do not always coincide with their everyday language practices.…”
mentioning
confidence: 99%
“…These insights are based on effective language acquisition pedagogy and practices, well documented in research, especially in wellstructured immersion and dual language programs. They include factors such as an enriched and life-meaningful setting, but not necessarily a formal one (Schwartz 2008;Schwarzer 2001); best pedagogy in language acquisition (Clark 2000) specifically related to the target language, as in my case, Chinese (Kuo and Hooper 2004;Nuo 2007;Winkler 2005); and a strong relational dynamics of the parties involved -administrators, teachers, parents, and children.…”
Section: S Lawmentioning
confidence: 98%